Nutritive Value and Rumen Degradation of Stover of Two Sorghum Varieties in Camels - H. A., Elsaid; M. E., Elimam; N. H. , Talib; S. M. , Elbasheer (Journal of Veterinary Medicine and Animal Production, 2022)
The new ruminant protein systems require information on feeds degradation characteristics. Currently in Sudan the information on rumen degradation of Sorghum Stover parts in camels is not available. Therefore, this study aimed to determine the rumen degradation and degradation characteristics of Stover of two Sorghum varieties namely; Wad Aakar and Feterita in order to improve camel’s nutrition and production. The two Sorghum stover varieties Wad Aakar and Feterita stalks were divided into upper (U), middle (M) and lower (L) parts. The proximate analysis of the parts was determined. Three rumen fistulated camels were used to study the rumen degradation. The animals were fed Medicago sativa (Barseem) ad libitum and 2kg concentrate ration daily. Artificial fibre bags (18x14cm) were incubated in the rumen for different times and degradation characteristics were calculated. The effective degradability at different rates of outflow from the rumen of two Sorghum stover parts was calculated. Results showed that Sorghum stover varieties varied in proximate analysis and degradation characteristics of different parts. However, in the two Sorghum varieties the upper part had the highest CP and ash while the lower part had the highest CF, EE and OM. The least EE was shown in the middle part of the both Sorghum stover. In all plant parts, the highest potential degradability was observed in CP, while the least was shown in OM compared to other contents. The effective degradability varied in different parts of Sorghum Feterita and Wad Akar stovers and decreased with increasing rates of outflow from the rumen. It is concluded that camels have high fibres rumen degradation, therefore, we recommend the use of crop residues for camels feeding.